ALTernative Functions for Human FANCM at Telomeres - Domingues-Silva, Beatriz; Silva, Bruno; Azzalin, Claus M. (Frontiers in Molecular Biosciences, 2019)
The human FANCM ATPase/translocase is involved in various cellular pathways including DNA damage repair, replication fork remodeling and R-loop resolution. Recently, reports from three independent laboratories have disclosed a previously unappreciated role for FANCM in telomerase-negative human cancer cells that maintain their telomeres through the Alternative Lengthening of Telomeres (ALT) pathway. In ALT cells, FANCM limits telomeric replication stress and damage, and, in turn, ALT activity by suppressing accumulation of telomeric R-loops and by regulating the action of the BLM helicase. As a consequence, FANCM inactivation leads to exaggerated ALT activity and ultimately cell death. The studies reviewed here not only unveil a novel function for human FANCM, but also point to this enzyme as a promising target for anti-ALT cancer therapy